Green wall as a strategy to reduce impacts environmental with recyclable materials in the CAAG - Camaño Tordecilla, Karen
Considering the importance of vertical green gardens at an environmental and landscapelevel and constantly seeking the implementation of ecological strategies for the Aquacultureand Agroindustrial Center of Gaira, the strategy of the 3R collection, reuse and recycling isestablished through a research project, that seeks the minimization of polluting materials forthe environment such as PET plastic bottles, since it is one of the great problems that arecurrently being generated due to their poor disposal. Within the development of this project,initial parameters of temperature and humidity are taken to the classroom located in theEnvironmental Unit of the Center, looking for relevant information that provides a starting point,later campaigns are carried out for the collection of PET bottles, contests and awarenesswithin of the apprentices, which allowed generating a greater sense of belonging. Once thelargest number of bottles had been collected, they were cleaned and organized, as well asthe selection of the varieties of ornamental plants typical of the region, and with the helpof instructors from the Center and apprentices, the activities of assembly of a vertical wall,preparation of the fertilizer for each of the pots, and planting of the plants, observing that inthe experimentation area a thermal comfort began to be felt by the apprentices, visitors andthe Center’s own, in addition to promoting in each of them the importance of recycling and theproper use of PET-type plastics, the use of vertical gardens